Thermodynamic analysis of Glycerol steam reforming - Dieuzeide, María Laura (2010)
A thermodynamic analysis of steam reforming of glycerol using the stoichiometric method has been performed. Since the aim of this work is to study product distribution and coke formation in equilibrium, two different models have been proposed: (a) CO as primary product and (b) CO2 as primary product. Moreover, substantial information regarding the behavior of the different reactions could be acquired. Product distribution at equilibrium has been investigated in a broad range of conditions: temperature (600-1200 K), water-to-glycerol feed molar ratio (0:1-10:1), and pressure (1-9 atm). Glycerol conversion results completely over the whole range of the mentioned conditions. Consequently, product distribution at equilibrium is determined by water gas shift (WGS) and methanation or methane steam reforming reactions. Finally, high temperatures and a high water-to-glycerol feed molar ratio favor hydrogen production and decrease both methane and coke.